NbB12−: a new member of half-sandwich type doped boron clusters with high stability. Issue 39 (25th September 2019) - Ren, Mengxue; Jin, Siyu; Wei, Donghe; Jin, Yuanyuan; Tian, Yonghong; Lu, Cheng; Gutsev, Gennady L.
Abstract : The global minimum structure of a NbB12 − cluster of half-sandwich type. Abstract : A theoretical study of geometrical structures and electronic properties of niobium-doped boron clusters is performed using the CALYPSO approach for the global minimum search followed by density functional theory calculations. It is found that the global minima obtained for the neutral clusters correspond to the half-sandwich structures at n = 10–17 and the tubular-type structures at n = 18–20. The geometrical patterns in the anion series are more complex. The geometries undergo a transformation from the wheel-like structure of NbB10 − to the half-sandwich ones beginning at n = 11 and finally to the drum-shaped structures at n ≥ 18. A fascinating NbB12 − cluster is uncovered by our structural search, which shows robust stability and can be considered as a new member of the half-sandwich transition metal doped boron clusters. The chemical bond analysis indicates that the high stability is due to the strong interactions between the Nb atom and the B12 host as well as to the strong B–B covalent bonds. Our study will enrich the database of geometrical structures of transition metal doped boron clusters and will stimulate future synthesis of boron-based nanomaterials.